Analysis and evaluation of the environmental impacts of 'upstream' petroleum operations. (2016) - Irhoma, Ammar; Su, Daizhong; Higginson, Martin
Sustainability is increasingly considered an essential business function, but in Libya, petroleum companies are slow to address operational issues that could reduce environmental concerns. This study aims to evaluate the environmental impacts of upstream petroleum operations. The methods adopted in the study are a literature review, an environmental impact assessment (EIA) study and qualitative analyses from, fieldwork trials and 56 semi-structured interviews. The results of the study show that the main environmental impacts are aquatic, terrestrial or atmospheric, with the most significant pollutants linked to the latter category, mainly from engine exhausts, turbine emissions, gas flaring and venting. Major environmental degradations are identified in Libyan upstream operations and a number of recommendations formulated minimising their effect. Particular importance is placed on establishing strict sustainability policies and regulations, and the implementation of an environmental management system.